(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Information Technology (IT) and research activities have driven growth and progress in IT. In terms of other efforts in science in other fields, IT has shown that it has one of the organizations and governments’ most financed research investments. This is because IT and its services have now been a key driver of profits and growth for many organizations.This article would aim to explore and address the methods of testing methodologies employed in IT Project Management studies. This paper also describes the strategy of the doctoral program for the management of information technology in a course in IT study methodology (DMIT).